The Soviet-British Relations at the Turn of 1917/1918: Key Issues and Untapped Opportunities - E. Yu. Sergeev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
This paper examines one of the key issues in relations between the Great Britain and the Bolshevik government during the first months after the October period of the Great Russian Revolution of 1917–1922 – participation of the Soviet Russia in military operations on the side of the Entente in the final stage of the First World War. The author emphasizes that position of the British political elites regarding the seizure of power in Russia by Vladimir Lenin and his supporters was not as straightforward as it was portrayed by the Soviet and Russian historiography: the British politicians faced a dilemma since they did not want to see Russia either as a neutral country or an enemy. On the basis of contemporaries’ memoirs and diaries, previously unstudied official documents as well as a comparative analysis of the Russian and Western historiography, especially the recent publications, the author assesses successes and failures of both the Foreign Office and the People’s Commissariat of Foreign Affairs in the late 1917 and early 1918 – the least studied period in the history of the Soviet-British relations. The paper shows that apart from a continuous fighting on the fronts of the Great War, these successes and failures were attributable to a number of factors, including political struggle in both countries, strategic foreign policy objectives of both the Bolsheviks and the British elites, as well as the interference of the third parties – be it allies or enemies. In this difficult context, practical steps of the foreign ministries of both countries primarily depended on the outcomes of the intense polemics between the British and the Bolshevist politicians, diplomats and opinion leaders. Special focus is on the relations between the Soviet Russia and Great Britain during the Brest peace negotiations and particularly on the mission of R.H. Bruce Lockhart. The author concludes that throughout this period neither side managed to win the diplomatic duel: Great Britain had lost its strategic ally whereas Russia after four years of struggle had to repel the military intervention of its ex-partners in the Entente.